2021
DOI: 10.3390/ijms22062814
|View full text |Cite
|
Sign up to set email alerts
|

The Esterase PfeE, the Achilles’ Heel in the Battle for Iron between Pseudomonas aeruginosa and Escherichia coli

Abstract: Bacteria access iron, a key nutrient, by producing siderophores or using siderophores produced by other microorganisms. The pathogen Pseudomonas aeruginosa produces two siderophores but is also able to pirate enterobactin (ENT), the siderophore produced by Escherichia coli. ENT-Fe complexes are imported across the outer membrane of P. aeruginosa by the two outer membrane transporters PfeA and PirA. Iron is released from ENT in the P. aeruginosa periplasm by hydrolysis of ENT by the esterase PfeE. We show here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…The distribution of virulence factors seems to be unrelated to the isolation source of analyzed P. aeruginosa strains ( Figure 3 ). In addition, about 50% of the analyzed strains showed the ability to degrade esculin in vitro ( Figure 3 ), and this phenotype could be related to the ability of these strains to acquire iron and produce siderophores [ 29 ]. Although not significant, some modifications in the distribution of soluble virulence factors were observed among P. aeruginosa strains, depending on their isolation source.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of virulence factors seems to be unrelated to the isolation source of analyzed P. aeruginosa strains ( Figure 3 ). In addition, about 50% of the analyzed strains showed the ability to degrade esculin in vitro ( Figure 3 ), and this phenotype could be related to the ability of these strains to acquire iron and produce siderophores [ 29 ]. Although not significant, some modifications in the distribution of soluble virulence factors were observed among P. aeruginosa strains, depending on their isolation source.…”
Section: Resultsmentioning
confidence: 99%
“…Upon binding of periplasmic ferri-siderophore to the PfeS sensor at the inner membrane, the transcriptional regulator PfeR is released, upregulating the transcription of the pfeA gene. 47,48 Induction of pfeA transcription in the presence of the conjugates indicates the penetration of the compounds, since an interaction with PfeS can occur only in the periplasm.…”
Section: Peptide-siderophore Conjugates Enter the Bacterial Periplasmmentioning
confidence: 99%
“…40 In the bacterial periplasm, the trilactone ring of the ferric-ENT is hydrolysed by the esterase PfeE into the Fe(III)-(DHBS)3 complex. 16,41 Iron release from this complex requires probably a reduction step by a yet non-identified reductase. In vitro studies have shown that only the hydrolysis of enterobactin PfeE is not enough to dissociate iron from DHBS, but a reduction of iron is also needed.…”
Section: Introductionmentioning
confidence: 99%
“…In the bacterial periplasm, the trilactone ring of the ferric ENT is hydrolyzed by the esterase PfeE into the Fe­(III)-(DHBS) 3 complex. , Iron release from this complex probably requires a reduction step by a yet non-identified reductase. In vitro studies have shown that only the hydrolysis of ENT by PfeE is not enough to dissociate iron from DHBS, but a reduction of iron is also needed. , This has been confirmed in Escherichia coli where the dissociation of iron from ENT involves a NADPH-dependent reductase YdjH and the esterase Fes. How iron is then transported further across the inner membrane into the bacterial cytoplasm remains unknown. The expression of PfeA and PfeE is induced by the presence of ferric ENT by a two-component regulation system PfeS/PfeR, where PfeS is the inner membrane sensor and PfeR the transcriptional activator (Figure ).…”
mentioning
confidence: 99%